IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH CONTEXT CLUES IN UNDERSTANDING READING TEXTS BY USING GOOGLE CLASSROOM AT GRADE XII MS 2 SMA NEGERI PLUS RIAU - Tengku Emadesti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this article was to explain the effect of context clues to improve students’ vocabulary mastery in understanding reading texts by using google classroom at grade XII MS 2 SMAN Plus Riau and factors influenced the improvement. Data were collected through checklist formats, field notes, and tests.  This classroom action research was conducted in two cycles constituting 3 meetings for each cycle. The result of this research revealed that the students’ vocabulary mastery in understanding reading texts by using google classroom increased in each cycle. In the first cycle, the percentage of students’ vocabulary mastery was 80.60%. However, this result was not satisfactory yet. Thus, the research was continued to cycle II. In the second cycle, the increase of students’ vocabulary mastery  was 90.08%. This implied that there is an increase of students’ vocabulary mastery in understanding reading texts  by using google classroom in second cycles. In conclusion, the use of context clues increased the students’ vocabulary mastery in understanding reading texts by using google classroom.